Descriptive Study of Optimizing Family Health Functions in Preventing COVID 19 Transmission - Iskim Luthfa; Nopi Nur Khasanah (Journal of Nursing Care, 2021)
COVID 19 has become a world health problem, and Indonesia has declared an emergency status for an outbreak. To prevent transmission of COVID 19, the government has set three policies that are increasing the availability and reliability of infrastructure, involving the industrial world and social education. However, COVID 19 transmission still occurs. Preparedness for COVID 19 transmission starts with the family as a minor system in the community. The Healthy Indonesian Program with a Family Approach is considered an excellent effort to carry out health functions to prevent COVID 19 transmission. This study aimed to optimize family functions in preventing COVID 19 transmission. This study used a descriptive-analytic design. Two hundred and fifty-eight samples were recruited using a consecutive sampling technique. To measure family function using a questionnaire. Data were analyzed by descriptive statistics (i.e., frequency statistics). The frequency statistics showed that most of the respondents have optimally performed family functions in the health sector. Most of the respondents understand COVID 19 (88,4%), they are capable of making decisions (96,9%), they can care for the family (88,8%), they can modify the environment (75,2%), and they can take advantage of health services (81%). This study only captures the extent to which the family optimally performs health functions; it does not provide any form of intervention. The results of this study prove that the family has an important role to play in breaking the transmission of COVID 19.